Optimalisasi Reformasi Pelayanan Kesehatan Melalui Program E-Health Pada Puskesmas Jagir Kota Surabaya - Muhammad Nasrullah; Anggraeny Puspaningtyas S.AP., M.AP (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Public service is the fulfillment of needs in society. there should be an increase in the quality of public services by utilizing information and communication technology, namely E- Government. The government's job is to provide services. For example, the Surabaya government is improving the quality of public services in the health sector with the e-health program. This study aims to see whether this program is effective for the people of Surabaya. The research method uses descriptive analysis, whether the e-health program is able to improve the quality of public services in the city of Surabaya in the health sector.